Nilai filosofis Serat Bima Suci - Purwadi, Purwadi (Kejawen, 2025)
Some problem of life according to Sirat Bima Suci must be solved wisely, effectively, efficiently, sufistic professional, and religious humanistic. Personification of Bima that search degree as satria pinandhita that do tapa rame or do social work religiously. The Unity between cipta, rasa, karsa, karya is the equilibrium to arrange the better future. The reflection of ethical philosophy existension of Serat Bima Suci is one of discourse of problem solving to some contemporary problems in social historical context.